Implementation of a Heuristic Algorithm for the Solution of Discrete Time Cost Trade-off Problem - Şengül, Ayşe Nur; Doğan, Nezir; Bettemir, Önder Halis (Intelligent Methods In Engineering Sciences, 2024)
Time cost trade-off problem aims to minimize the total project cost by crashing the critical activities. This problem is solved by mathematical programming and meta-heuristic algorithms. However, construction sector has minimum priority on the theoretical knowledge to implement robust optimization algorithms. For this reason aforementioned optimization algorithms can be hardly implemented for the private construction companies. The nature of the time cost trade-off algorithm is not challenging and can be solved heuristically. In this study, a spreadsheet application is developed by utilizing in-app excel functions to identify the critical activities of the project and the paths of the project. The construction schedule is entered to the spreadsheet application as acticity on arrow diagram and the logical relationships between the activities are defined. Forward and backward pass computations are given as formulations which includes the actual activity durations. The developed application calculates the crashing costs of the critical activities and highlights the activities with the cheapest crashing costs. Prepaperd spreadsheet application implements a heuristic solution algorithm which is based on minimum cost slope of the construction activities. The user can easily execute the proposed or user selected crashing alternative and the schedule is updated according to the selection. The application is tested on 6 activity project and the optimum solution is obtained by crashing the activities sequentially. The proposed technique can be utilized to reduce the total project cost of the construction sector.